Capital Structure, CEO Dominance, and Corporate Performance - Pornsit Jiraporn (2018)
We use agency theory to investigate the influence of CEO dominance on variation in capital structure. Due to agency conflicts, managers may not always adopt leverage choices that maximize shareholders' value. Consistent with the prediction of agency theory, the evidence reveals that, when the CEO plays a more dominant role among top executives, the firm adopts significantly lower leverage, probably to evade the disciplinary mechanisms associated with debt financing. Our results a re important as they demonstrate that CEO power matters to critical corporate outcomes such as capital structure decisions. In addition, we find that the impact of changes in capital structure on firm performance is more negative for firms with more powerful CEOs. Overall, the results are in agreement with prior literature, suggesting that strong CEO dominance appears to exacerbate agency costs and is thus detrimental to firm value. © 2011 Springer Science+Business Media, LLC.